Process modelling (bpm) in healthcare - Terras Marques, Inês (2022)
Terras Marques, I., Santos, C., & Santos, V. (2020). Process modelling (bpm) in healthcare : breast cancer screening. In M. Antona, & C. Stephanidis (Eds.), Universal Access in Human-Computer Interaction: Design Approaches and Supporting Technologies. 14th International Conference, UAHCI 2020, Held as Part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19–24, 2020, Proceedings, Part I (pp. 98-109). (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics); Vol. 12188 LNCS). Springer. https://doi.org/10.1007/978-3-030-49282-3_7